Предмет: Алгебра,
автор: alezsey2283
(a-3)²+(6-a)²+2(a-3)(6-a) решите бырей плиз
Ответы
Автор ответа:
0
(a-3)²+(6-a)²+2(a-3)(6-a) =а² -6а +9 + 36 - 12а + а² +2(6а -а²-18 +3а) = 2а² -18а + 45 +12а -2а² -36 +6а = 9
Автор ответа:
0
(a-3)²+(6-a)²+2(a-3)(6-a)=а^2-6а+9+36-12а+а^2+2(6а-а^2-18+3а)=а^2-6а+9+36-12а+а^2+12а-2а^2-36+6а=9
Похожие вопросы
Предмет: Русский язык,
автор: WildPanda
Предмет: Русский язык,
автор: alinazaripova24
Предмет: Математика,
автор: nik13121990
Предмет: Физика,
автор: 79221206505